Proposed interior design of district retail and gallery at 93, Jln Maarof Bangsar Baru, Bangsar 59000 Kuala Lumpur for district Sdn. Bhd. / Muhammad Akmal Arifin - Arifin, Muhammad Akmal (Faculty of Architecture, Planning and Surveying, 2012)
As to complete my final study as Diploma in Interior Design, my project final project is about to Proposed New Interior Design of District Shop & Gallery for District. The location is at the Ipoh, Perak. The project chosen because the potential that i can see through the concept that they provide. Unfortunately, among the things that has been i discovered is that the retail is facing design problem and need to solve the traffic airflow. Other issues is the images in the retail, it should be more attractive and also have the aura that can attract people. So in the new branch of the district shop will come with the new concept but still remain the main the real concept, just the design is change a little bit. The shop is providing the service sell and shows their artwork. It is because they showing the artwork of the street style like the graffiti art.